Pemahaman Caregiver Dalam Mengakses Layanan Kesehatan Di Komunitas Pada Orang Dengan Skizofrenia Yang Mengalami Risiko Perilaku Kekerasan : Caregiver Understanding in Accessing Health Services in the Community for People with Schizophrenia Who Are at Risk of Violent Behavior - Aditya, Nora; Guntur, Ahmad; Ulfa, Miftakhul; Soebagijono (Chakra Brahmanda Lentera Institute, 2023)
Cancer sufferers in Indonesia increase 20% every year, namely at 136.2 per hundred thousand population. This boosted Indonesia's ranking, which is eighth in Southeast Asia and 23rd in Asia. In this community service to form a group of health cadres in the community with the aim of optimizing their role, increasing knowledge and ability to perform breast self-examination as an effort to prevent breast cancer. This group-based activity is carried out in a structured and comprehensive manner. The methods used are lectures, demonstrations, and practice. While the media used are materials, video screenings, simulations with visual aids, and BSE leaflets. The material presented included the incidence of breast cancer, understanding, risk factors, myths about breast cancer, the importance of BSE, when BSE is performed and how or steps to check it. The health cadres who came were 43 people from 11 community units (RW) in the Bandarharjo Village, North Semarang. Cadre groups according to their RW. After the community service activities were carried out, the cadres experienced an increase in knowledge about BSE by 85%, cadres were able to carry out the simulation correctly according to the steps 90%. Cadres conduct counseling and BSE simulations to residents with an agreed schedule. This activity is carried out regularly according to the agreed schedule between residents and health cadres. Forming a group of health cadres who care about BSE is very effective for breast cancer prevention. It is hoped that this activity can continue along with the regeneration of the health cadres themselves.